2002
DOI: 10.1016/s0092-8674(02)00875-9
|View full text |Cite
|
Sign up to set email alerts
|

An EGFR/Ebi/Sno Pathway Promotes Delta Expression by Inactivating Su(H)/SMRTER Repression during Inductive Notch Signaling

Abstract: The Notch and Epidermal Growth Factor Receptor (EGFR) pathways both regulate proliferation and differentiation, and the cellular response to each is often influenced by the other. Here, we describe a mechanism that links them in a sequential fashion, in the developing compound eye of Drosophila. EGFR activation induces photoreceptor (R cell) differentiation and promotes their expression of Delta. This Notch ligand then induces neighboring cells to become nonneuronal cone cells. ebi and strawberry notch (sno) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
198
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(207 citation statements)
references
References 66 publications
7
198
2
Order By: Relevance
“…The suppressing deficiencies Df(2L)net-PMF (21A1;21B8) and Df(2L)al (21B8;21D1) contain the genes kismet and ebi, respectively (Table 2). Both kismet and ebi are involved in chromatin remodeling and are positive regulators of dEGFR and Ras signaling in the retina (Therrien et al 2000;Tsuda et al 2002). Mutations in either locus suppressed GMR-dRet phenotypes.…”
Section: Men2amentioning
confidence: 99%
“…The suppressing deficiencies Df(2L)net-PMF (21A1;21B8) and Df(2L)al (21B8;21D1) contain the genes kismet and ebi, respectively (Table 2). Both kismet and ebi are involved in chromatin remodeling and are positive regulators of dEGFR and Ras signaling in the retina (Therrien et al 2000;Tsuda et al 2002). Mutations in either locus suppressed GMR-dRet phenotypes.…”
Section: Men2amentioning
confidence: 99%
“…Given that EGFR activation appears to contribute more than just a permissive survival signal in the developing eye, the ability of undifferentiated cells to respond differently to the same signal has led to the suggestion of a combinatorial code that integrates EGFR-mediated inputs with other factors to specify all the necessary cell types (Freeman, 1997;Kumar and Moses, 1997;Hayashi and Saigo, 2001;Tsuda et al, 2002). Because the larval eye imaginal disc contains a temporal gradient of ommatidial maturity, reflecting the progression of the MF, perhaps the particular factors that make up the code are expressed at different positions relative to the MF.…”
Section: Egfr Signaling Is Required For All Eye Cell Fates Except R8:mentioning
confidence: 99%
“…Somehow cells must already know the appropriate response when stimulated by a particular combination of such semipermissive instructions. To explain this, researchers have proposed that the exact response of undifferentiated cells to a particular combination of RTK and Notch signals changes over time (Freeman, 1997;Kumar and Moses, 1997;Hayashi and Saigo, 2001;Tsuda et al, 2002). If this is true, then there must be distinct "competence zones" posterior to the MF, with changes in cellular competence governed by the expression of different transcription factors.…”
Section: Combinatorial Code Specifying Photoreceptor Fatementioning
confidence: 99%
See 1 more Smart Citation
“…Inducers of cell stress, including arsenic trioxide and anisomycin, can also activate MEKK1 and are potent inhibitors of SMRT function; this MEKK1-dependent mechanism may contribute to the prodifferentiation effects of arsenic trioxide as used in the treatment of acute promyelocytic leukemia (44). The Drosophila EGF receptor has also been shown to regulate the function of the Drosophila SMRTER protein, although whether SMRTER is a true ortholog of mammalian SMRT remains unclear (66). Reciprocally, it has been reported that N-CoR, but not SMRT, can be inhibited in certain contexts in response to TAB2 and Akt pathways operating downstream of cytokine and ciliary neurotrophic factors (51,61).…”
Section: Mekk1 Is One Of Several Signals Operating Downstream Of Growmentioning
confidence: 99%